Faktor – Faktor yang Berhubungan dengan Loneliness dan Social Isolation pada Lansia: Systematic Literature Review - Hertalenta Agustin Larosa; Dhia Zahwa Fadhiela Andriani; Dwinita Sahalina; Rahmadianti Aulia (Jurnal Ilmu Psikologi dan Kesehatan | E-ISSN : 3063-1467, 2026)
The aging population highlights loneliness and social isolation as crucial psychosocial issues impacting mental health. This study identifies factors associated with these conditions through a Systematic Literature Review (SLR). Using the PRISMA protocol on ScienceDirect and PubMed databases (2021–2026), 8 empirical articles were selected. The review indicates that loneliness and social isolation consistently increase the risk of depression, anxiety, and stress, while decreasing older adults' subjective well-being. The quality of social relationships (social connectedness and social capital) along with psychological resilience (optimism and resilience) act as more effective protective factors than the mere quantity of social networks. Interventions targeting specific barriers, such as hearing loss, prove more effective in overcoming isolation. Neurobiological findings further confirm that loneliness triggers neurological responses to social pain caused by social rejection. Efforts to improve older adults' well-being